Mandiri Unbk Try Out Information System Web Based Using Linear Congruent Method At Madrasah Working Group (Kkm) Mts N 2 Demak - Murtadho's Word; Fujiama D. Silalahi (Journal of Technology Informatics and Engineering, 2023)
The try out process is an exam simulation exercise every year before the National Examination conducted by school institutions. The main objective of this exercise is as an effort of school institutions to prepare students to get maximum scores on the National Examination.Madrasah Working Group (KKM) of MTs 2 Demak is a body within the Ministry of Religion which fosters coordinative cooperative relations between Demak MTs 2 and private Madrasahs in the area of ​​Demak 2 MTs. So far the Try Out system at the KKM level still uses manual procedures and is still off line using paper. As a result of this system, there are still delays in the distribution of questions and reports at the central level. In making Try Out questions, randomization of questions only uses the package method questions A, B and C, so there are still students who give each other answers.LCM (linear congruent method) is a method of generating random numbers on the Try Out. The principle of this method is where the form of the LCM number as the scrambler of the question, including increament (c), modulus (m), multiplier (a), and initial value (Z0), which has provisions: c = 0 ≤ c <m, m = 0 <m, a = 0 <a <m, and Z0 = 0 ≤ Z0 <m. Making this application using the PHP programming language and database used is MySql with the R & D system development method according to Borg and Gall, including: Research and information collecting, Planning, Develop prelminary form of product, Preliminary field testing, Main product revision, Main field testing , Operational product revision, Operational field testing, Final product revision, Dissemination and implementation.Madrasah Working Group (KKM) Demak MTs 2 in conducting a try out system still uses the manual offline method and the problem scrambler is only limited to packages A, B, and C, then with the Try Out Information System the web-based KKM level is expected to facilitate parties KKM and tighten students to avoid fraud.